Role of quercetin and arginine in ameliorating nano zinc oxide-induced nephrotoxicity in rats - Faddah Laila M; Baky Nayira A; Al-Rasheed Nouf M; Al-Rasheed Nawal M; Fatani Amal J; Atteya Muhammad (BMC, 2012)
Abstract Background Nanoparticles are small-scale substances (<100 nm) with unique properties. Therefore, nanoparticles pose complex health risk implications. The objective of this study was to detect whether treatment with quercetin (Qur) and/or arginine (Arg) ameliorated nephrotoxicity induced by two different doses of nano zinc oxide (n-ZnO) particles. Method ZnO nanoparticles were administered orally in two doses (either 600 mg or 1 g/Kg body weight/day for 5 conscutive days) to Wister albino rats. In order to detect the protective effects of the studied antioxidants against n-ZnO induced nepherotoxicity, different biochemical parameters were investigated. Moreover, histopathological examination of kidney tissue was performed. Results Nano zinc oxide-induced nephrotoxicity was confirmed by the elevation in serum inflammatory markers including: tumor necrosis factor alpha (TNF-α), interleukin-6 (IL-6); and C-reactive protein (CRP). Moreover, immunoglobulin (IGg), vascular endothelium growth factor (VEGF), and nitric oxide (NO) were significantly increased in rat serum. Serum urea and creatinine levels were also significantly increased in rats intoxicated with n-ZnO particles compared with the control group. Additionally, a significant decrease in the non-enzymatic antioxidant reduced glutathione (GSH) was shown in kidney tissues and serum glucose levels were increased. These biochemical findings were supported by a histopathological examination of kidney tissues, which showed that in the animals that received a high dose of n-ZnO, numerous kidney glomeruli underwent atrophy and fragmentation. Moreover, the renal tubules showed epithelial desquamation, degeneration and necrosis. Some renal tubules showed casts in their lumina. Severe congestion was also observed in renal interstitium. These effects were dose dependent. Cotreatment of rats with Qur and/or Arg along with n-ZnO significantly improved most of the deviated tested parameters. Conclusions The data show that Qur has a beneficial effect against n-ZnO oxidative stress and related vascular complications. Also, its combination with Arg proved to be even more effective in ameliorating nano zinc oxide nephrotoxicity.